P-MAPA and interleukin-12 reduce cell migration/invasion and attenuate the toll-like receptor-mediated inflammatory response in ovarian cancer SKOV-3 Cells: A preliminary study - Lupi, Luiz Antonio [UNESP] (2020)
Immunotherapies have emerged as promising complementary treatments for ovarian cancer (OC), but its effective and direct role onOCcells is unclear. This study examined the combinatory effects of the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride, known as P-MAPA, and the human recombinant interleukin-12 (hrIL-12) on cell migration/invasion, apoptosis, toll-like receptor (TLR)-mediated inflammation, and cytokine/chemokine profile in human OC cell line SKOV-3. P-MAPA and IL-12 showed cancer cell toxicity under low doses after 48 h. Although apoptosis/necrosis and the cell cycle were unchanged by the treatments, P-MAPA enhanced the sensitivity to paclitaxel (PTX) and P-MAPA associated with IL-12 significantly reduced the migratory potential and invasion capacity of SKOV-3 cells. P-MAPA therapy reduced TLR2 immunostaining and the myeloid differentiation factor 88 (MyD88), but not the TLR4 levels. Moreover, the combination of P-MAPA with IL-12 attenuated the levels of MyD88, interferon regulatory factor 3 (IRF3) and nuclear factor kappa B (NF-kB p65). The IL-12 levels were increased and P-MAPA stimulated the secretion of cytokines IL-3, IL-9, IL-10, and chemokines MDC/CCL22 and, regulated on activation, normal T cells expressed and secreted (RANTES)/CCL5. Conversely, combination therapy reduced the levels of IL-3, IL-9, IL-10, MDC/CCL22, and RANTES/CCL5. Collectively, P-MAPA and IL-12 reduce cell dynamics and effectively target the TLR-related downstream molecules, eliciting a protective effect against chemoresistance. P-MAPA also stimulates the secretion of anti-inflammatory molecules, possibly having an immune response in the OC microenvironment.